Optimization of the thermal performance of the double skin roof - Ng, Yi Li. (2013)
The purpose of the study is to promote a greener society by cutting down on electric consumption as power generation will produce greenhouse gases. One of the methods to reduce electric consumption is by reducing the usage of air-conditioners. This can be achieved by optimizing the double skin roof and hence, increase the buildings’ heat insulation.